A prospective study of alcohol consumption and renal cell carcinoma risk. Issue 1 (10th December 2014) - Karami, Sara; Daugherty, Sarah E.; Purdue, Mark P.
Abstract : Recent epidemiological studies suggest that alcohol consumption may reduce renal cell carcinoma (RCC) risk, although inconsistent findings have been reported by sex and alcoholic beverage type. To better understand the relationship between alcohol consumption and RCC risk, we conducted an analysis within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. We followed up participants in the analytic cohort ( N  = 107, 998) through 2010 for incident RCC ( N  = 408), and computed hazard ratios (HRs) and 95% confidence intervals (CIs) for alcohol intake using Cox regression with adjustment for age, sex, race, study center, hypertension, body mass index, and smoking status. In this study population increasing alcohol consumption was associated with reduced RCC risk compared to non‐drinkers (>9.75 g day −1 : HR, 0.67; 95%CI, 0.50 to 0.89; p trend = 0.002). We observed similar patterns of association for men and women as well as by alcohol beverage type. In analyses stratified by smoking status, the inverse association with consumption was apparent for ever smokers (HR, 0.51; 95%CI, 0.36 to 0.73; p trend<0.0001) but not among never smokers (HR, 1.08; 95%CI, 0.66 to 1.76; P trend = 0.78; p interaction = 0.01). Our study findings offer further support that alcohol consumption is associated with reduced RCC risk, regardless of sex or alcoholic beverage type. The finding of interaction with smoking is novel and requires confirmation. Abstract : What's new? For multiple cancers, increasing alcohol intake is associated with increasing risk, but in the case of renal cell carcinoma (RCC), the inverse may be true. The present study analyzed alcohol intake and RCC risk, taking into account various factors, including sex, smoking status, and beverage type. RCC risk was reduced markedly in association with increasing alcohol consumption, for both men and women and regardless of beverage type. Analyses of smoking status uncovered a possible interaction between RCC risk, alcohol intake, and smoking. Additional studies are needed to understand the mechanism behind the association between alcohol intake and RCC risk.